PENGARUH BRAND IMAGE DAN CUSTOMER SATISFACTION TERHADAP LOYALITAS KONSUMEN - Yayuk Gina Andria; Yulius Wahyu Setiadi (UM. Bengkulu, 2023)
This study aims to determine the effect of Brand Image and Customer Satisfaction on Consumer Loyalty in Purchasing Skecherss for Management Students at Muhammadiyah University of Bengkulu. This research was conducted on Management Students of the University of Muhammadiyah Bengkulu, the population used in this study was Management Students class of 2018 University of Muhammadiyah Bengkulu, the number of samples used was 110 respondents, using incidental sampling technique, namely the number of indicators multiplied by 10. The data that has been collected is processed using the Classical Assumption Test Technique, Multiple Linear Regression Analysis Technique, Coefficient of Determination Analysis (R2), and Partial Test (t-test), Simultaneous Test (f-test). The results of this study indicate that partially the Brand Image variable has a significant effect on the Consumer Loyalty variable, H1 is accepted and Customer Satisfaction has a significant effect on the Consumer Loyalty variable, H2 is accepted. While the Brand Image (X1) and Customer Satisfaction (X2) tests have a significant effect on Consumer Loyalty (Y) of Management Students at Muhammadiyah Bengkulu University so that H3 is accepted. Keywords: Brande Image, Customer Satisfaction and Consumer Loyalty.